Uso de tecnologias digitais na formação para o cuidado ao paciente: uma nova onda na educação farmacêutica - Silva, Rafaella de Oliveira Santos (2021)
Throughout its history, the pharmaceutical profession has gone through different phases of development (so-called also waves) that have promoted its evolution and adaptation to the different demands of humanity. In recent decades, the expansion of pharmacy practice has included patient care, with the increasing use of active teaching and learning methodologies, including digital technologies (e.g. digital serious game and Virtual Patient -VP- software), in the development of knowledge, skills, and attitudes. However, there are few high-level evidence studies on the use of these tools in pharmaceutical education, as well as their impact on the new generation of students and professionals. Thus, this Thesis aims to describe the effect of digital technologies (digital serious game and VP software) on the training of pharmacy students and pharmacists for patient care. This study was carried out in three stages. In the first stage, a manuscript (commentary) was prepared with the objective of understanding the integration of digital technologies as a new wave in pharmacy practice and education. In the second stage, a systematic review was carried out on the effect of digital serious game related to patient care in the development of knowledge, skills, and attitudes in pharmaceutical education. In the third stage, a systematic review was elaborated on the effect of VP software on the development of knowledge, skills, and attitudes in pharmaceutical education. Both searches were carried out in the Cochrane, ERIC, Embase, IPA, LILACS, Pubmed, Scopus, and Web of Science databases using words related to “pharmaceutical education”, “pharmacists” and “pharmacy students”. In addition, words related to “games”, “serious games” and “digital games” were used in the second stage; and, words related to “virtual patient” were used in the third stage. From the reflections made in the commentary, it was noted that the pharmacy profession can no longer wait for the expansion and integration of digital technologies in pharmacy practice and education. The achievement of this goal requires both disruptive professors and the development of specific knowledge, skills, and attitudes (clinical and digital). The systematic review on the digital serious game related to patient care in pharmaceutical education identified 1,521 studies, of which seven were included. In most studies, there was no improvement in knowledge, skills, and attitudes (n=6; 85.73%) and user satisfaction with the tool was negative (n=5; 71.43%). Furthermore, in general, the methodological quality of these studies was below ideal. The systematic review on the VP software in pharmaceutical education identified 1,260 studies, of which 29 were included. In most studies, there was an improvement in knowledge, skills, and attitudes (n=26; 89.65%) and user satisfaction with the tool was positive (n=28; 96.55%). In addition, in general, the methodological quality of these studies was satisfactory. From the findings of this Thesis, it was possible to observe that digital technologies, such as digital serious game and VP software, can be innovative tools to be included in the curricula for the development of knowledge, skills, and attitudes related to patient care in view of the learning characteristics of the new generation of pharmacy students and pharmacists.